Rapt/Wrapped Listening: The Aesthetics of “Surround Sound” (Sound Stage Screen, 2021)
This essay is prompted by “surround sound,” the sonic results of which have been evident in cinemas since the late 1970s and the encoding for which, in the form of Dolby 5.1 on the soundtracks of DVDs, since the turn of the century has been fairly ubiquitous. By way of background, the essay deals in turn with the physical nature of three-dimensional listening and with the history of stereophonic sound as manifest both in the cinema and on LP recordings. More to the point, the essay deals with the aesthetic differences (not just perceptual but also affective) between listening to three-dimensional sounds in real life situations and listening to re-creations of those sounds, via a Dolby system or otherwise, in the privacy and comfort of one’s home. Playing on the homophonic adjectives in its title, the essay reflects on why sometimes we give more rapt attention to artificial versions of “surround sound” than to the genuine stereophonic sound in which we are literally wrapped almost on a daily basis.
Keywords: Dolby 5.1; Surround Sound; Stereo; Terrence Malick; Fantasound